2002
DOI: 10.1093/cercor/12.4.349
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities of SNARE Mechanism Proteins in Anterior Frontal Cortex in Severe Mental Illness

Abstract: A fundamental molecular component of neural connectivity is the SNARE (SNAP receptor) protein complex, which consists of three proteins, syntaxin, SNAP-25 and VAMP. Under appropriate conditions, the SNARE complex can be formed in vitro. To investigate the hypothesis that dysregulation of SNARE proteins or their interactions could be abnormal in severe mental disorders, the three SNARE proteins and the complex were studied in post-mortem anterior frontal cortex homogenates. An ELISA was used to quantify SNARE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
1
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(92 citation statements)
references
References 74 publications
4
83
1
3
Order By: Relevance
“…75 Further expression studies of proteins involved in neurite formation in these diseases are required to strengthen a hypothesis such as this. It is worth noting that previous expression studies in SCZ and BPD generally reported a tendency towards a reduced expression in SCZ and BPD, 76,77 with increases in some synaptic-associated proteins, such as SNAP-25 60 and conflicting reports regarding other such as GAP-43 and synaptophysin. 37,[78][79][80][81][82] A strength of the current investigation is the use of two complementary proteomic approaches, 2D DIGE and GeLC-MS/MS to identify candidate diseaseassociated proteins within the MM proteome in SCZ and BPD.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…75 Further expression studies of proteins involved in neurite formation in these diseases are required to strengthen a hypothesis such as this. It is worth noting that previous expression studies in SCZ and BPD generally reported a tendency towards a reduced expression in SCZ and BPD, 76,77 with increases in some synaptic-associated proteins, such as SNAP-25 60 and conflicting reports regarding other such as GAP-43 and synaptophysin. 37,[78][79][80][81][82] A strength of the current investigation is the use of two complementary proteomic approaches, 2D DIGE and GeLC-MS/MS to identify candidate diseaseassociated proteins within the MM proteome in SCZ and BPD.…”
Section: Discussionmentioning
confidence: 91%
“…55 Several studies have examined syntaxin expression in SCZ and have demonstrated an increase in the mRNA level in the temporal cortex 56 and in protein levels in the cingulate cortex. 57,58 However, no changes were reported in total syntaxin protein expression in the parietal cortex, 57 temporal cortex, 57 frontal cortex 57,59,60 or the cerebellum 61 in SCZ. Future studies would need to examine (i) the relationship of STXBP1 with syntaxin and SNARE complex formation as well as (ii) the expression of both proteins across several brain regions in SCZ.…”
Section: Discussionmentioning
confidence: 96%
“…A previous study reported a significant increase of SNAP25 and syntaxin interaction in subjects who died by suicide. 31 Thus, we carried out an additional analysis taking into account the suicide status of subjects. However, no significant effect of suicide status was observed on this sample (Student's t-test, P SNAP25a = 0.58 and P SNAP25b = 0.36).…”
Section: Expression Analysismentioning
confidence: 99%
“…These samples were used in previous studies, and descriptions of individual cases are available. 31,39 We used well-characterized antibodies reactive with MAG (Boehringer Mannheim, Laval, Canada) 40 and with CNPase (SMI-91, Sternberger, Lutherville, MD, USA). 34 Prior to using an ELISA to quantify the oligodendrocyte-associated proteins MAG and CNPase, we performed immunoblotting studies of human brain homogenates, which confirmed the expected single band at approximately 100 kDa for MAG and the doublet band at approximately 45-50 kDa for CNPase.…”
Section: Mri Studiesmentioning
confidence: 99%